TINJAUAN ATAS PEMANFAATAN INSENTIF PAJAK PENGHASILAN PASAL 21 MENURUT PMK NO.9 TAHUN 2021, DI WILAYAH BOGOR PADA MASA PANDEMI COVID-19 - Rizal Riyadi; Yeni Elfiza Abbas (Jurnal Ilmiah Hospitality, 2022)
Tax incentives are efforts made by the government in relation to economic recovery in Indonesia from the impact of the Covid-19 virus pandemic which can be in the form of deductions, exemptions or delays in paying taxes so that economic activity can develop. In Indonesia, tax incentives are issued based on the prevailing regulation of the minister of finance, so the regulation will be extended in line with the decision of the minister of finance. That there are several regulations that will be changed or added to every policy of the applicable finance ministerial regulation.The purpose of this review is to evaluate and find out how many registered taxpayers take advantage of tax incentive facilities, especially the Income Tax Article 21 DTP tax incentive during the Covid-19 pandemic in the Bogor area. And being able to know about these tax incentives can help taxpayers or business actors in increasing the level of confidence and optimism in the business world.The results of the review show that the number and percentage of taxpayers who use tax incentives recorded at the Regional Office of the Directorate General of Taxes West Java III as of May 2021 are still small. Therefore, it is necessary to carry out more massive socialization activities regarding tax incentive facilities.